MIND-MAPPING AS A TECHNIQUE IN TEACHING WRITING DESCRIPTIVE PARAGRAPH - Puspita, Ni Made Rina; Marbun, Rismaya; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The purpose of this research is to know whether the use of mind-mapping technique is effective or not and how significant the effectiveness of the use of mind-mapping on the second grade students of SMP Kristen Kanaan Kubu Raya in academic year 2014/2015. This research was a pre-experimental study. The sample was Class VIII students. The data were collected by administring the pre-test and the post-test. Based on the data, the students’ mean score of pre-test was 56.3 and the students’ mean score of post-test was 76.2. Then the data were analyzed by using Effect Size (ES) formula. The research finding shows that the effect size of the treatment is 1.32 (0.2<ES>0.8). It is categorized as high. It indicates that mind-mapping is highly-effective to teach writing descriptive paragraph on class VII students. Key words: Mind-mapping, pre-experimental study. Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat keefektifan mind-mapping dalam pengajaran menulis paragraph deskriptif kepada siswa kelas 8 SMP Kristen Kanaan Kubu Raya tahun ajaran 2014/2015. Penelitian ini adalah sebuah penelitian pre experimental. Sampel dalam penelitian ini adalah siswa kelas 8. Data-data diambil dengan menerapkan pre-test and post-test. Berdasarkan dari data, nilai rata-rata siswa pada pre-test adalah 56.3 dan nilai rata-rata siswa pada post-test adalah 76.2. Kemudian data dianalisis dengan menggunakan rumus ES (Effect Size). Hasil penelitian menunjukkan bahwa efek dari penggunaan mind-mapping adalah 1.32 (0.2<ES>0.8>. Hasil ini dikategorikan memiliki efek yang tinggi. Hal ini menandakan bahwa mind-mapping sangat efektif dalam pengajaran menulis paragraf deskriptif kepada siswa kelas 8. Kata kunci: Mind-mapping, penelitian pre-experimental.